THE ROLE OF FOSTER CAREGIVERS IN THE EFFECTIVENESS OF ONLINE LEARNING IN PESANTREN - Muhammad Mushfi El Iq Bali; Noer Holilah (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
The role of foster care in the pesantren is a solution for the pesantren in optimizing all work programs and activities of the pesantren, especially in online learning that is carried out in the pesantren. This study is more focused on the guardianship system of Madrasah Ibtidaiyah students under the age of 11 who carry out online learning in Islamic boarding schools. This research uses a qualitative approach with the type of case study at the Pondok Pesantren Nurul Jadid, especially in the Fathimatuzzahro area. The results showed that in online learning carried out in Islamic boarding schools, foster caregivers have several roles that help make online learning more effective. First, the foster caregivers act as badals of the parents of their foster children. Second, the foster caregivers act as badal for the teacher/teacher of their foster children. Third, foster caregivers act as facilitators for their foster children. Fourth, foster caregivers become uswah for students who become their foster children. It is hoped that this will help the pesantren to streamline and maximize online learning at the pesantren to achieve the educational goals expected by all parties.